2003
DOI: 10.1093/ptj/83.8.696
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Function After Total Knee Arthroplasty

Abstract: Background and Purpose. Decreasing hospital stays for patients with total knee arthroplasties (TKAs) have a direct effect on rehabilitation. The identification of modifiable determinants of postsurgical functional status would help physical therapists plan for discharge from hospitals. The purpose of this study was to identify preoperative determinants of functional status after a TKA. Participants. Using a community-based, prospective cohort study, data were collected from 276 patients who received a primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
150
5
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(175 citation statements)
references
References 33 publications
13
150
5
7
Order By: Relevance
“…In contrast to other studies, the variables 'age' and 'sex' were not related to an increase in problems reported in the period after discharge (Meleis & Lindgren 2001, Jones et al 2003, Buurman et al 2010, Rytter et al 2010). This may be due to the fact that our study considered only medium-or low-intensity elective surgery, so old or fragile patients formed a small proportion of the study participants.…”
Section: Problems Postdischargecontrasting
confidence: 98%
“…In contrast to other studies, the variables 'age' and 'sex' were not related to an increase in problems reported in the period after discharge (Meleis & Lindgren 2001, Jones et al 2003, Buurman et al 2010, Rytter et al 2010). This may be due to the fact that our study considered only medium-or low-intensity elective surgery, so old or fragile patients formed a small proportion of the study participants.…”
Section: Problems Postdischargecontrasting
confidence: 98%
“…15 Retrospective cohort study n = 8050 SF-12 SF-12 Higher odds of less functional gain were correlated to BMI over 40, lower preoperative MCS, each 5 year increase in age, poor or fair quadriceps strength and non-OA diagnosis Gandhi et al 16 Prospective cohort study n = 551 SF-36 SF-36, WOMAC Poorer mental health state were predictive of a less sustained functional outcome on both the WOMAC and SF-36 scale Heck et al 17 Prospective cohort study n = 291 SF-36 SF-36, WOMAC Better preoperative mental state and worse pre-operative knee function were the most important factors that were correlated to improvement in physical health. Jones et al 18 Prospective cohort study…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Previous studies investigating the effect of preoperative psychological distress on post-operative function after different types of joint replacement show conflicting results. 4,[12][13][14][15][16][17][18][19][20][21][22] Furthermore, Howard et al 23 recently published a review investigating psychological factors possibly influencing outcomes after joint replacement pooling data for knee and hip joint replacements. However, since patients undergoing hip and knee joint replacement differ in age, gender and duration of disease, 24 comparison among these patients is not methodologically sound.…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of studies suggest that poor preoperative functional status is associated with poorer outcome in terms of both function and pain after total joint arthroplasty [1][2][3][4][5]. This has important implications, particularly for women who, in a number of studies, have been shown to have more disability at the time of surgery and a willingness to accept greater decline in function before considering surgery [6][7][8][9][10].…”
mentioning
confidence: 99%